Intensive science and virtual philosophy - Delanda, Manuel (Continuum, 2002)
Intensive Science and Virtual Philosophy cuts to the heart of the philosophy of Gilles Deleuze and of today's science wars. At the start of the 21st Century, Deleuze is now regarded as the most radical and influential of contemporary philosophers. Yet his work is widely misunderstood and misinterpreted. In this already classic work Manuel DeLanda does what the growing host of Deleuzians have falled to do - he makes sense of Deleuze for both analytic and continental thought, for both science and philosophy.